THE EFFECTIVENESS OF BENSON RELAXATION TECHNIQUE AND SLOW DEEP BREATHING ON SLEEP QUALITY IN POST-CARDIAC SURGERY PATIENTS - Nia Khusniyati; Tuti Herawati; Amelia Amelia; Hermin Esti Dyaningtyas (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Patients recovering from cardiac surgery often experience pain, anxiety, and sleep disturbances. The Benson Relaxation Technique, a muscle relaxation method that influences the hypothalamus and reduces sympathetic and parasympathetic activity, has shown positive effects on respiratory function, heart rate, and cardiac workload, ultimately promoting better sleep quality.The purpose of this study was to assess the effectiveness of the Benson Relaxation Technique combined with slow deep breathing exercises in improving sleep quality among patients following cardiac surgery.Methods: This quasi-experimental study involved 50 post-cardiac surgery patients, divided into two groups: 25 in the intervention group and 25 in the control group. The intervention group practiced the Benson Relaxation Technique combined with slow deep breathing exercises, performed three times. Sleep quality was assessed using the GSQS (Groningen Sleep Quality Scale) questionnaire. Data were analyzed using an independent t-test with SPSS software.Results: Statistical analysis showed a significant improvement in sleep quality in the intervention group, with a p-value of 0.001. The independent t-test yielded a p-value of 0.002 and a mean difference of 0.960 between the intervention and control groups, indicating a meaningful effect of the relaxation technique on sleep quality.Conclusion: The Benson Relaxation Technique combined with slow deep breathing is effective in improving sleep quality among post-cardiac surgery patients. This non-pharmacological intervention can be recommended as a supportive therapy during recovery to enhance patient well-being and accelerate healing.